Avanços, propriedades e aplicações de dispersões sólidas no desenvolvimento de formas farmacêuticas sólidas - Lariza Darlene Santos Alves; Magaly Andreza Marques de Lyra; Larissa Araújo Rolim; Geisiane Maria Alves Presmich; Pedro José Rolim-Neto (São Paulo State University (UNESP), 2012)
Amorphous solid dispersions feature widely in strategies to improve the bioavailability of poorly water-soluble compounds. However, there are few reports of this technique being used in finished products, demonstrating a need for in depth knowledge of the main and most recent production techniques used on the laboratory and industrial scale, as well as of the main physicochemical characteristics of the most widely used hydrophilic polymers, listing their advantages and disadvantages and potential applications. In this review, it is intended to discuss the recent advances regarding solid dispersions and their use in multicomponent systems.